HUMAN POTENTIAL PRESERVATION POLICY-MAKING IN UKRAINE IN THE MIDST OF WAR: CATALYSTS FOR YOUTH RE-EMIGRATION - Taras Vasyltsiv; Olha Mulska; Ruslan Lupak; Iryna Biletska; Vitalii Boiko; Ulana Ivaniuk (Proceedings on Engineering Sciences)
The study presents the results of a sociological survey based on a questionnaire using Google Forms. The minimum sample size is calculated based on the resampling (amounts to 2,040 people). The survey was conducted in the largest recipient countries of Ukrainian human resources (the Republic of Poland, Germany, the Czech Republic, Italy, etc.). The main destimulators of the re-emigration of young people from the EU include high quality of life and decent working conditions abroad, adequate level of social security, and socio-economic stability. The article proves that the level of aspirations of Ukrainian youth to stay abroad for a longer period is quite high. A real desire to continue their lives in economically developed EU countries, on the one hand, and security factors and socio-economic uncertainty in Ukraine, on the other hand, are the main reasons for the development of these aspirations. Decent working and employment conditions, the absence of barriers and the promotion of professional and international mobility, opportunities to start one’s own business, a favorable business environment, and high living standards are the main catalysts for the re-emigration of young people to Ukraine.